2017
DOI: 10.1002/adma.201700072
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Large‐Area 2D Mo2C on In Situ Grown Graphene

Abstract: As a new member of the MXene group, 2D Mo C has attracted considerable interest due to its potential application as electrodes for energy storage and catalysis. The large-area synthesis of Mo C film is needed for such applications. Here, the one-step direct synthesis of 2D Mo C-on-graphene film by molten copper-catalyzed chemical vapor deposition (CVD) is reported. High-quality and uniform Mo C film in the centimeter range can be grown on graphene using a Mo-Cu alloy catalyst. Within the vertical heterostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
272
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(299 citation statements)
references
References 26 publications
(33 reference statements)
13
272
0
Order By: Relevance
“…Importantly, the α‐Mo 2 C crystals showed a crystal thickness‐dependent superconductivity and strong anisotropy with magnetic field orientation . In another report by Geng et al, a molten Mo‐Cu alloy catalyst was used in the CVD process to grow well‐faceted Mo 2 C single crystals on graphene. The Mo 2 C crystals were ~50–100 μm in width and ~8 nm in thickness and were vertically aligned on graphene .…”
Section: Mxenes Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the α‐Mo 2 C crystals showed a crystal thickness‐dependent superconductivity and strong anisotropy with magnetic field orientation . In another report by Geng et al, a molten Mo‐Cu alloy catalyst was used in the CVD process to grow well‐faceted Mo 2 C single crystals on graphene. The Mo 2 C crystals were ~50–100 μm in width and ~8 nm in thickness and were vertically aligned on graphene .…”
Section: Mxenes Synthesismentioning
confidence: 99%
“…In another report by Geng et al, a molten Mo‐Cu alloy catalyst was used in the CVD process to grow well‐faceted Mo 2 C single crystals on graphene. The Mo 2 C crystals were ~50–100 μm in width and ~8 nm in thickness and were vertically aligned on graphene . During the growth, graphene could passivate the catalyst surface and prevent the Mo atoms from reacting with methane, resulting in a change of growth mechanism from precipitation‐limited to diffusion‐limited process.…”
Section: Mxenes Synthesismentioning
confidence: 99%
“…Experimentally,Mo 2 CMXene have been proved to exemplify high HER activity,b ut the overpotential reached up to 0.283 V. [26] In order to broaden the applications of Mo 2 C, large-area 2D Mo 2 Co n graphene was synthesized and it unveiled ar elatively low overpotential of 87 mV compared to the previous work. [27] More recently,Y uan et al reported that MXene nanofibers exhibited excellent electrocatalytic HER activity due to the presence of ample active sites in materials surface, thusi mplying that Ti-based MXene renders am agnificent prospect in the energy application. [28] Furthermore, theoretical study indicated that the HER catalytic activity of MXenes can be facilely tuned by controlling the layer thickness and Oc overage.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Density functionalt heory (DFT) calculations showed that the hybridizationb etween do rbitals of metal molybdenum and sa nd po rbitals of carbon broadened of the dband of Mo 2 C, and thus led to as imilard -band structure to Pt. [29][30][31][32] The Pt-like electronic structure of Mo 2 Cm akei ta promising substitute for expensive Pt-based catalysts.Conventionally,M o 2 Cw as synthesized by temperature programmed reduction methods with gas-solid reactionsb etween metal, [33,34] or metal-oxides olids, [35][36][37] and carbon-rich gases (e.g.,C H 4 /H 2 ,C O/H 2 ,C 2 H 6 /H 2 ,e tc.). However,e xcessive carbon tendst ob edeposited from the carbon-containing gases and lead to polymeric carbon speciesc overed active sites, which could reducet he HERe lectrocatalytic activity.…”
mentioning
confidence: 99%
“…Conventionally,M o 2 Cw as synthesized by temperature programmed reduction methods with gas-solid reactionsb etween metal, [33,34] or metal-oxides olids, [35][36][37] and carbon-rich gases (e.g.,C H 4 /H 2 ,C O/H 2 ,C 2 H 6 /H 2 ,e tc.). However,e xcessive carbon tendst ob edeposited from the carbon-containing gases and lead to polymeric carbon speciesc overed active sites, which could reducet he HERe lectrocatalytic activity.…”
mentioning
confidence: 99%